Increasing the Prediction Power of Preterm Labor using Interleukin 6 and Fetal Fibronectin as Alarming Signals in Symptomatic Patients - Hussain, Amal Abdul Muhsen; Sharif, Yasamin Hamza (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Giving birth at preterm is considered as a bothering problem to both healthcare systems and pregnant women around the world, causing alarming levels of mortality. To avoid this issue, certain biological markers can be employed for early detection to predict the occurrence of the PTD (PTD) ahead of time for giving better medical care to the pregnant women who at risk of PTD. Objective: The current study was performed to evaluate the power of using interleukin-6 (IL-6) and fetal fibronectin (fFN) present in the cervicovaginal fluid (CVF) as predictors of the symptomatic PTD patients. Patients & Methods: In this study, 91 pregnant hospital attendees (24-34 weeks; 18-45 years old) with suggested PTD symptoms, such as abdominal pain and uterine contraction and with cervical length of less than 25mm, were participated. To detect IL-6 and fFN, vaginal swabs were collected for performing an ELISA test to later follow up with the patients within 48hrs, seven days, and 14 days from the first day of admission to the hospital. Results: No significant association between PTD with patients age, parity, BMI, and gestational age, but significant association with previous history of PTD. There was significant association between PTD and increase the level of CVF fFN and IL-6 with best cut-off value for CVF fFN is(>45ng/ml) with (95%CI of 0.763-0.918) and accuracy of 85.2% with a sensitivity of 73.1% and specificity of 95.6% which is of high significant value (P≤0.01).While CVF of IL-6 (>231pg/ml) with (95% CI of 0.630- 0.820), with accuracy of 73.3%, sensitivity of 50% and specificity of 96.9% which was statistically significant finding (P≤0.01).The predictive value of combined fFN and IL-6 in women at risk of preterm labor was 84.6% with sensitivity 84.6%,specificity 92.3%, positive predictive value (PPV) 81.5%, negative predictive value (PPV) 93.8% and accuracy of 90.1%. Conclusion: Each of fFN or IL-6 located in the CVF may provide a strong predictor of PTD; however, this prediction capability may provide an even stronger signal of detecting PTD ahead of time if both biomarkers requested at the same time.